2017
DOI: 10.1155/2017/1380367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dam Depth and Relief Track Depth on Steady-State and Dynamic Performance Parameters of 3-Lobe Pressure Dam Bearing

Abstract: The present study analyzes the effect of pressure dam depth and relief track depth on the performance of three-lobe pressure dam bearing. Different values of dam depth and relief track depth are taken in nondimensional form in order to analyze their effect. Results are plotted for different parameters against eccentricity ratios and it is shown that the effect of pressure dam depth and relief track depth has great significance on stability and other performance parameters. Study of stability and performance ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Further, it is observed that threshold speed increases up to ε = 0.25 and then decreases gradually for increase in eccentricity ratio. The maximum threshold speed is observed at an eccentricity of 0.25, which is in agreement with the optimum range given by Kumar and Kakoty (2017) for Newtonian lubrication. Results from Tables 2 and 3 confirm the discussions presented in Figures 3–7.…”
Section: Discussion Of Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Further, it is observed that threshold speed increases up to ε = 0.25 and then decreases gradually for increase in eccentricity ratio. The maximum threshold speed is observed at an eccentricity of 0.25, which is in agreement with the optimum range given by Kumar and Kakoty (2017) for Newtonian lubrication. Results from Tables 2 and 3 confirm the discussions presented in Figures 3–7.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…The influence of elastohydrodynamic on selected dynamic characteristics of an inverted three-lobed bearing with a pressure dam was reported by Batra et al (2012). Kumar and Kakoty (2017) concluded that when the relief track ratio is selected between 0.2–0.6, the stability of three-lobe dam bearing can be achieved. Nicholas et al (1980) experimentally found the best eccentricity is 0.25 to obtain a better threshold for pressure dam bearing.…”
Section: Introductionmentioning
confidence: 99%
“…There are so many other viscosity models to observe variation in viscosity but Krieger–Dougherty viscosity model is valid for a wide range of volume fractions of nanoparticle. As per the Krieger–Dougherty viscosity model 37 where φm is the maximum volume fraction and η is the intrinsic viscosity with a typical value of 2.5 for singular dispersion of rigid spherical particles. 38 The volume fraction of nanoparticle is taken as 0.005 and different nondimensional couple stress parameters as 0, 0.2, 0.4, and 0.6.…”
Section: Theorymentioning
confidence: 99%
“…Optimum oil groove location of two-lobe bearings affects the performance of bearings. 18 Kumar and Kakoty 19 evaluated the performance of three-lobe pressure dam bearings using finite difference method. They suggested that by incorporating dam and relief track, stability and threshold speed increases.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that by incorporating dam and relief track, stability and threshold speed increases. Results of researchers 1519 indicated an enhancement in the performance of pressure dam bearings by incorporating dam in the upper lobe and relief track in the lower lobe of a non-circular hydrodynamic journal bearing, while operating with Newtonian lubrication.…”
Section: Introductionmentioning
confidence: 99%